THE EFFECT OF HARD FACING PROCESS ON THE HARDNESS AND MICROSTRUCTURE OF BUCKET TOOTH FOR DIFFERENT MANGANESE CONTENT - Suryo Darmo; Braam Delfian Prihadianto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
High hardness and wear resistance of bucket tooth are required in the face of abrasion and impact. High manganese steel is hard and ductile, making it more suitable for bucket tooth materials. Bucket tooth can wear out and need to be returned to their original size, so that bucket tooth that have been eroded must be coated with a hard material, using a hard facing process. In this study, the hard facing process was carried out in bucket tooth containing 10.4%, 11.60%, 12.70%, 13.60%, and 14.60% men (manganese) elements, using hard facing electrodes of the AWS A5.13 (JIS Z 3251). Hard facing process was using SMAW welding with an average heat input of 1087.43 J/mm. The hard facing process shown that the hardness of weld metal was always lower than of HAZ (Heat Affected Zone) and base metal. The hardness of the weld metal was almost the same for all types of the bucket tooth, which was about 233.478 HVN.